2021
DOI: 10.1002/cpdd.926
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction Among Ezetimibe, Rosuvastatin, and Telmisartan

Abstract: To evaluate the pharmacokinetic interactions among rosuvastatin, ezetimibe, and telmisartan, a randomized, open-label, 3period, 6-sequence crossover study was conducted in healthy subjects. Subjects received one of the following treatments once daily for 7 days in each period with a 1-week washout: a fixed-dose combination of ezetimibe/rosuvastatin 10/20 mg, telmisartan 80 mg, combination therapy of ezetimibe/rosuvastatin 10/20 mg, or telmisartan 80 mg. Blood samples were collected up to 24 hours postdose at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Another possible explanation is due to drug–drug interactions. Pharmacokinetic analysis of the three drugs showed a 16–26% increase in telmisartan concentrations in healthy volunteers [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is due to drug–drug interactions. Pharmacokinetic analysis of the three drugs showed a 16–26% increase in telmisartan concentrations in healthy volunteers [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 A bioequivalence (BE) study of EZE/rosuvastatin fixed-dose tablets in healthy Japanese subjects revealed that there was no clinically relevant effect of food on EZE and EZEG exposure. 11 In addition, the coadministration of EZE and telmisartan has been suggested to inhibit UGT1A3, increase the peak drug concentration (C max ) at steady state 12,13 of EZE, and decrease the C max at steady state 12 of total EZE.…”
mentioning
confidence: 99%